The role of linguistic and cognitive skills in reading Chinese as a second language: A path analysis modeling approach - Yang, Lei; Xiong, Ying; Chen, Qi (Frontiers in Psychology, 2023)
This study examined the role of basic linguistic skills (vocabulary, syntax, orthography, and morphological awareness), basic cognitive skills (working memory), and upper level cognitive skills (inference making and reading monitoring) in reading Chinese as second language (L2). A total of 252 international students from Pakistan, Indonesia, Malaysia, and Laos were recruited and a range of measures including a Chinese reading comprehension test (HSK level 3), four linguistic knowledge tests on Chinese lexical, syntactic, and orthographic knowledge as well as morphological awareness, a reading span test, an inference making task, and an inconsistency detection test. The results of hierarchical multiple regressions showed that the measured linguistic skills and cognitive skills explained 80% of the variances in L2 Chinese reading, among which morphological awareness made the largest contribution. The path analysis revealed that linguistic skills and working memory contributed indirectly to reading comprehension via inference making and comprehension monitoring, while the two upper level cognitive skills made direct contributions. Overall, this study demonstrates that inference making and comprehension monitoring contributed directly to reading comprehension, while linguistic skills and working memory functioned indirectly via the upper level cognitive skills and highlights the importance of morphological awareness in a hierarchical model of L2 Chinese reading.